已知(2011+y-x)(x-y-2009)=-2010,求(2011+y-x)²+(2009+y-x)²的值
人气:316 ℃ 时间:2019-10-17 02:54:08
解答
(2011+y-x)(x-y-2009)=-2010
-(2011+y-x)(2009+y-x)=-2010
(2011+y-x)(2009+y-x)==2010
令a=2011+y-x,b=2009+y-x
所以a-b=2
平方
a²-2ab+b²=4
所以(2011+y-x)²+(2009+y-x)²
=4+2ab
=4+2×2010
=4024
推荐
- 已知{x+2y=2009, y+2z=2010, z+2x=2011,则x+y+z=_______.
- 已知A=2010X+2009,B=2010X+2010,C=2010X+2011,求(a-b)²+(b-c)²+(c-a)²的值.
- 已知x^3+x^2+x+1=0,求x^2009+x^2010+x^2011的值
- 已知x+y=2009,y+2z=2010,z+2x=2011,则x+y+z=多少
- 已知x^2+x=-1 你能求x^2013+x^2012+x^2011+x^2010+x^2009+…+x^4+x^3+x^2+x+1的值吗?
- He ___(teach) you English well,doesn't he?
- 露西用英语怎么说?We can't put our bikes over there.改祈使句
- 闻一多(打一字)
猜你喜欢